2008
DOI: 10.1063/1.2913169
|View full text |Cite|
|
Sign up to set email alerts
|

Ring-breaking electron attachment to uracil: Following bond dissociations via evolving resonances

Abstract: Calculations are carried out at various distinct energies to obtain both elastic cross sections and S-matrix resonance indicators (poles) from a quantum treatment of the electron scattering from gas-phase uracil. The low-energy region confirms the presence of pi(*) resonances as revealed by earlier calculations and experiments which are compared with the present findings. They turn out to be little affected by bond deformation, while the transient negative ions (TNIs) associated with sigma(*) resonances in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 38 publications
7
70
0
2
Order By: Relevance
“…In addition to the poor characterization of the possible higher-lying resonances in pyrimidine DNA bases, previous studies [18][19][20][22][23][24][25] have struggled to produce parameters of, especially, the third (highest-lying) π * resonance in satisfactory agreement with experimental values. For this reason, Winstead and McKoy investigated elastic electron collisions with a model molecule, pyrazine.…”
Section: The Calculations Of Winstead and Mckoy Found Evidence Forsupporting
confidence: 65%
See 2 more Smart Citations
“…In addition to the poor characterization of the possible higher-lying resonances in pyrimidine DNA bases, previous studies [18][19][20][22][23][24][25] have struggled to produce parameters of, especially, the third (highest-lying) π * resonance in satisfactory agreement with experimental values. For this reason, Winstead and McKoy investigated elastic electron collisions with a model molecule, pyrazine.…”
Section: The Calculations Of Winstead and Mckoy Found Evidence Forsupporting
confidence: 65%
“…These are significantly narrower than the σ * resonance characterized by Gianturco et al in their uracil work 19 and our analysis indicated that they probably have some core-excited character; nonetheless one of these might be the pyrazine equivalent of the σ * uracil resonance. An extremely wide resonance (as postulated by Burrow et al), would probably be undetectable by simple examination and fitting of the eigenphase sums.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…13,15 Such discrepancies between DEA and electron transfer experiments have already been detected in other molecules, most notably regarding the NCO − yield in uracil and thymine. 23 Briefly, it was shown that, owing to the presence of the potassium cation in the vicinity of the molecular anion, a delay in the autodetachment process of the extra electron occurs, allowing π * orbitals to be populated long enough for the electron to be transferred to a highly dissociative σ * orbital, 23,35 which will subsequently lead to fragmentation. Indeed, a recent DEA study to D-ribose shows a resonance profile for OH − formation consisting of one dominant peak at near-zero energy and a weak wider structure at around 7 eV, the latter assigned to a shape resonance.…”
Section: B Oh −mentioning
confidence: 99%
“…2 In a subsequent Comment, 3 Burrow pointed out that the claimed agreement depended on misidentifying the first and second calculated * resonances with, respectively, the second and third experimental resonances. A recent paper by Gianturco et al 4 reports new calculations for uracil employing substantially the same scattering model and again claims close agreement with experimental * resonance positions, and also with those of other calculations. 5,6 Although the resonance positions that Gianturco et al obtain ͑1.7, 3.5, and 6.5 eV͒ ͑Ref.…”
mentioning
confidence: 50%